Regulatory requirements in Japan and its compliance monitoring programmes - Someya, Hitoshi (Henry Stewart Talks, 2012)
Complexity of Japanese GLP monitoring programmes, Review and comparison of all four GLP programmes, Detailed explanation of medical products programme, Compliance Monitoring Authority, legal bases, and regulatory requirements of medical products programme, Normal practices and follow-ups of GLP inspection in medical products programme